2016
DOI: 10.1177/1753465816661930
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with experience of fatigue, and functional limitations due to fatigue in patients with stable COPD

Abstract: Background:The aim of this study was to determine the influence of selected physiological, psychological and situational factors on experience of fatigue, and functional limitations due to fatigue in patients with stable chronic obstructive pulmonary disease (COPD).Methods:In total 101 patients with COPD and 34 control patients were assessed for experience of fatigue, functional limitation due to fatigue (Fatigue Impact Scale), physiological [lung function, 6-minute walk distance (6MWD), body mass index (BMI),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
68
1
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 57 publications
(76 citation statements)
references
References 61 publications
(111 reference statements)
5
68
1
2
Order By: Relevance
“…Nevertheless, our study also showed that other demographic factors, including age, education level and living alone, were inconsistently associated. These results were consistent with those reported in previous studies on fatigue in patients with COPD . It is worth noting, however, the lack of significant statistical effects of “living alone”, despite its relevance (around 4 times the OR of exhaustion).…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…Nevertheless, our study also showed that other demographic factors, including age, education level and living alone, were inconsistently associated. These results were consistent with those reported in previous studies on fatigue in patients with COPD . It is worth noting, however, the lack of significant statistical effects of “living alone”, despite its relevance (around 4 times the OR of exhaustion).…”
Section: Discussionsupporting
confidence: 92%
“…Therefore, exhaustion has been mostly described in relation to health conditions, like heart disease or stroke, and it is considered an entity separate from other symptoms . In contrast, exhaustion remains poorly investigated in COPD as an entity extreme of fatigue, because mostly, all range of the experience of fatigue has been studied like a whole . Recently, exhaustion has been described in its own right, because interest has increased in the fragility syndrome, in which exhaustion is a basic characteristic …”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations